IDENTIFIKASI KONSENTRASI CO, CO2, NO2, SO2, DAN PM10 YANG TERUKUR DI STASIUN GAW BUKIT KOTOTABANG SELAMA MUDIK LEBARAN TAHUN 2019-2023 - Zulistyawan, Kiagus Ardi (Megasains, 2023)
West Sumatra is regarded as one of the provinces that serves as a prominent location for the annual Eid homecoming tradition among migrants in Indonesia. In addition to this, West Sumatra serves as a popular tourist destination for individuals seeking leisure and recreation during the Eid holidays. Therefore, the rise in population activity and vehicle volume is expected to result in an escalation in air pollution levels. Furthermore, the influence of air pollution on respiratory health disorders is also substantial. Hence, the primary objective of this study is to ascertain alterations in the atmospheric concentrations of Carbon monoxide (CO), Carbon dioxide (CO2), Nitrogen dioxide (NO2), Sulphur dioxide (SO2), PM10 pollutants over the Eid period from 2019 to 2023 in the region of West Sumatra. The designated time intervals are H-10 following the conclusion of Eid and H+10. The data utilized in this study is derived from observations conducted at the Global Atmosphere Watch Bukit Kototabang Station. The findings of this study indicate that the observance of Eid activities has a discernible impact on the elevation of concentrations of carbon monoxide (CO), carbon dioxide (CO2), and nitrogen dioxide (NO2). In the interim, it has been shown that PM10 concentrations tend to be altered by ENSO conditions. However, there was no significant change seen in the SO2 parameter concerning population activity within the specified time frame. The parameters' conditions during 2019-2023 remain within the favourable category.